Econometric and decision analysis studies in research and development in the electronics industry - Thomas, Howard (The University of Edinburgh, 1970)
This thesis is an attempt to contribute to the understanding of the research and development process at the level of the firm. The existing economic evidence on research and development lacks thorough understanding of the nature of the inventive process, even though the volume sponsored by the National Bureau of Economic Research, "The Rate and Direction of Inventive Activity", points to the strikingly micro-character of R and D activity. The thesis has several major objectives:- First, to review the existing economic evidence on research and development and to point to any firm conclusions from the evidence. Second, to describe the nature of research and development in the firm, the characteristics of the inventive process and the decision process in R and D and the nature of uncertainty inherent in R and D activity. Third, to accumulate retrospective evidence on the efficiency of research and development in the firm. Fourth, to try and build operationally useful models to help R and D management cope with the sequential,groping and uncertain nature of R and D activity. These models stress the use of concepts from statistical decision theory and capital budgeting and are based on the decision process analysis work carried out in the firms. Fifth, to evaluate the usefulness and relevance of the rational theories of statistical decision theory in aiding the solution of the R and D decision under uncertainty. The thesis is divided into five parts which present results under each of the five above headings. Throughout the emphasis is on econometric and decision analysis work and parts (ii) to (v) are based on empirical evidence obtained from a case study sample of firms in the electronics industry in Scoreland. The final section discusses the usefulness of the research work and suggests further model-building approaches. Decision theory is found to be more useful on a conceptual- rather than on a practical level because of the uncertain character of R and D activity.